Medium-term oncological outcomes of intermediate-risk prostate cancer treated with HIFU or cryotherapy. A single center 10-year experience - Nuno Dias; Lara Rodriguez-Sanchez; Gianmarco Colandrea; Petr Macek; Xavier Cathelineau (Archivio Italiano di Urologia e Andrologia, 2022)
Objectives: Focal therapies (FTs) are promising techniques for the treatment of localized prostate cancer. We assessed the medium-term oncological outcomes of intermediate-risk prostate cancer (PCa) treated with HIFU or cryotherapy. Materials and methods: One-hundred and fifty consecutive patients with intermediate-risk PCa, treated between 2009 and 2018 at a single center were included. Primary study outcome was failure-free survival (FFS), defined as absence of additional treatment, systemic progression or prostate cancer related death. Results: Thirty-seven (25%) patients underwent cryotherapy and 113 (75%) HIFU. Median age was 69 (IQR 62-72) years, with 36 (24%) presenting palpable disease on rectal examination, and median total PSA of 7.85 (IQR 5.75-10.62) ng/mL. Patients were followed for a median of 61 (IQR 48-82) months. FFS at 2 and 4 years was of 75.6% and 53.6%, respectively. Survival from whole gland or systematic treatment at 2 and 4 years was of 78.9% and 53.9%, respectively. Patients with FFS presented lower total PSA nadir (1.89 vs 3.25 ng/mL, p < 0.001), higher % PSA reduction at 3 months (66.1% vs 49.3%, p < 0.001), and at nadir (75.5% vs 55.8%, p < 0.001). Other characteristics such has the treatment modality, age, prostate size, initial total PSA, cT stage, International Society of Urological Pathology (ISUP), tumor location and biopsy results by region did not differ between patients failing and not failing FT. Complications were uncommon (13%), with only onr (1%) patient having Clavien-Dindo grade > II. No deaths due to treatment were registered. Conclusions: At medium-term, FTs for intermediate-risk PCa presented good oncological results, with an excellent safety profile.